ANALYSIS OF DRINKING WATER SUPPLY IN TANJUNGPINANG CITY BY USING SYSTEM DYNAMICS MODELING (A CASE STUDY OF PDAM TIRTA KEPRI) - SUAIDI ( NIM : 25712308), ADI
Drinking water service in Tanjungpinang by PDAM Tirta Kepri until 2012 only by 42,27 %, whereas total population continues to grow more years. This condition suggests that water supply is still limited when compared to water demand. PDAM should determine the policy to overcome the water shortage beginning to be felt by most people in Tanjungpinang. The phenomenon of water demand is influenced by many factors, among which is growth of population, raw water scarcity, idle capacity, and water loss. This research aims to analyze the water demand in Tanjungpinang through the intervention of policy from supply sector with a combination of System Dynamics-AHP approach. System Dynamics (SD) provide a comprehensive problem solving with a good understanding of the phenomenon of forming elements and linkages between each element. SD models allows the determination of possible scenarios as input for decisions and policies in company. Whereas AHP is useful to compare the various alternative policies based on performance expressed by SD models and as prioritise of policy taken by decision makers. Scenario of drinking water supply in Tanjungpinang is done by customer restriction, alternatives of water resources, restore the function of protected forest, and lowering of distribution leakage.